Faktor yang Memengaruhi Gejala Dermatitis Kontak pada Tangan Pekerja Wet Work di Rumah Sakit dan Kampus UKRIDA - Calista, Talicia; Liem, Jen Fuk; Susanto, Djap Hadi (Jurnal Kedokteran Meditek, 2025)
Introduction: Contact dermatitis is one of the occupational skin diseases caused by exposure to irritants or allergens. This condition can arise during work activities or may be influenced by other factors within the work environment. Purpose: The purpose of this study was to determine the frequency of contact dermatitis symptoms on the hands and to identify factors associated with these conditions among workers engaged in wet work (such as cleaning, laundry, and kitchen) at Ukrida Hospital and Campus in West Jakarta.  Methods: This study utilized an analytic cross-sectional design conducted from August to September 2024. Individual characteristics and job information were collected through a questionnaire, while symptoms of contact dermatitis were assessed using the Nordic Occupational Skin Questionnaire 2002 (NOSQ-2002). Data were analyzed using the chi-squared test, the Mann-Whitney U test, and logistic regression. Results:  A total of 44 workers (45.8%) experienced symptoms of contact dermatitis on their hands, with the most common symptoms including dry, rough, scaly, itchy, and chapped skin. The study found that wet work and a history of allergies are associated with these symptoms of contact dermatitis.  Conclusion: Workers in wet environments and those with a history of allergies are at a higher risk of experiencing symptoms of contact dermatitis on their hands.  Implementing exposure control measures in the workplace is essentialn to managing symptoms of contact dermatitis.